2023
DOI: 10.1038/s41598-023-31691-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in intuitive and deliberative cooperation

Abstract: Cooperation is one of the most advantageous strategies to have evolved in small- and large-scale human societies, often considered essential to their success or survival. We investigated how cooperation and the mechanisms influencing it change across the lifespan, by assessing cooperative choices from adolescence to old age (12–79 years, N = 382) forcing participants to decide either intuitively or deliberatively through the use of randomised time constraints. As determinants of these choices, we considered pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Given that the internalization of strategies optimal for daily life varies based on social context, there is a pressing need for future research to explore cross-cultural differences. Moreover, apart from two exceptions that studied the cognitive underpinnings of cooperative behavior among adolescents (Nava et al, 2023) and children (Corbit et al, 2023), this research has mainly targeted adults. An essential future research avenue would be to trace the development of heuristics across different life stages.…”
Section: Limits On Generalitymentioning
confidence: 99%
“…Given that the internalization of strategies optimal for daily life varies based on social context, there is a pressing need for future research to explore cross-cultural differences. Moreover, apart from two exceptions that studied the cognitive underpinnings of cooperative behavior among adolescents (Nava et al, 2023) and children (Corbit et al, 2023), this research has mainly targeted adults. An essential future research avenue would be to trace the development of heuristics across different life stages.…”
Section: Limits On Generalitymentioning
confidence: 99%
“…Cooperative behavior involves the interaction of two or more people who work together towards a common goal, with mutual benefits for everyone ( Gutiérrez-Roig et al, 2014 ; Nava et al, 2023 ). Some studies have suggested that the tendency to show cooperative behaviors could change with age ( Garaigordobil and García de Galdeano, 2006 ; Gilar Corbi et al, 2008 ; Eisenberg et al, 2010 ; Belli et al, 2012 ; Smith et al, 2013 ; Gutiérrez-Roig et al, 2014 ; Keil et al, 2017 ; Taheri et al, 2018 ; Castellano Navarro et al, 2019 ; Zhang et al, 2019 ; Nava et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative behavior involves the interaction of two or more people who work together towards a common goal, with mutual benefits for everyone ( Gutiérrez-Roig et al, 2014 ; Nava et al, 2023 ). Some studies have suggested that the tendency to show cooperative behaviors could change with age ( Garaigordobil and García de Galdeano, 2006 ; Gilar Corbi et al, 2008 ; Eisenberg et al, 2010 ; Belli et al, 2012 ; Smith et al, 2013 ; Gutiérrez-Roig et al, 2014 ; Keil et al, 2017 ; Taheri et al, 2018 ; Castellano Navarro et al, 2019 ; Zhang et al, 2019 ; Nava et al, 2023 ). In this direction, adolescents show a higher tendency to cooperate than children ( Fuentes and Fernández, 1993 ; Gutiérrez-Roig et al, 2014 ; Keil et al, 2017 ; Castellano Navarro et al, 2019 ), while adults show more cooperative behaviors than adolescents ( Belli et al, 2012 ; Taheri et al, 2018 ; Zhang et al, 2019 ; Nava et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations